Listening to the Language of the Bible : hearing it through Jesus' ears - Tverberg, Lois.; Okkema, Bruce (Holland, MI : En-Gedi Resource Center, 2004)
The Bible speaks in words and phrases that come from a very different culture, place, and time. Hebraic ideas and imagery may sound foreign to our ears, but when we enter the minds of its ancient authors, we discover great new depth and meaning for our lives.
Includes bibliographical references (p. 139-150) and indexes.
Keywords: Bible -- Language, style; Bible -- Criticism, interpretation, etc; Devotional literature